Hedge fund course - McCrary, Stuart A. (J. Wiley, 2005)
A self-study course that reviews the technical and quantitative knowledge necessary to properly manage a hedge fund Today, traditional asset managers are looking to develop their own hedge funds as alternative offerings to their clients. Hedge Fund Course presents all the technical and quantitative knowledge necessary to run a leveraged investment company, and complements the less-technical information presented in the popular, How to Create and Manage a Hedge Fund (0-471-22488-X).